2019
DOI: 10.1002/jbm.a.36631
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid small‐diameter tube fabricated from decellularized aortic intima‐media and electrospun fiber for artificial small‐diameter blood vessel

Abstract: Hybrid small‐diameter tubes were fabricated by wrapping decellularized aortic intima‐media sheets around a tubular stainless steel mandrel with diameter 4 mm, and then by coating with electrospun segmented polyurethane. The synthetic coat was deposited uniformly to a thickness of about 0.5–3.5 μm depending on the duration of electrospinning. Resistance to luminal pressure, burst strength, and stiffness increased with the thickness of the electrospun coat, suggesting that the synthetic fabric reinforces the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…There was no obvious inflammatory response at the implantation site of decellularized PDL and mandible bone, indicating that there was no immune rejection. We previously reported that strong acute inflammation did not occur when HHP-decellularized porcine tissue was implanted into rabbits, rats, and mice [10,11,12,13,14,15,16,17]. Thus, HHP-decellularized mouse mandible bone with PDL is tolerated by rat host cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no obvious inflammatory response at the implantation site of decellularized PDL and mandible bone, indicating that there was no immune rejection. We previously reported that strong acute inflammation did not occur when HHP-decellularized porcine tissue was implanted into rabbits, rats, and mice [10,11,12,13,14,15,16,17]. Thus, HHP-decellularized mouse mandible bone with PDL is tolerated by rat host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Many techniques for decellularization have been developed and the appropriate method is selected based on the tissue of interest [4,5,6,7,8,9]. We previously reported that high hydrostatic pressure (HHP) decellularization, in which cells are ruptured by HHP and cell components are washed out, can effectively decellularize tissues such as blood vessel [10,11,12,13], cornea [14,15], and bone and bone marrow [16,17] while preserving the tissue structure. Additionally, HHP-decellularized tissues showed good biocompatibility and regenerative capacity.…”
Section: Introductionmentioning
confidence: 99%
“…However, human arteries are stiffer than porcine aortas and other porcine arteries. [104][105][106] Wu et al circumvented the mechanical mismatch across the two species by covering the porcine aorta graft with electrospun polyurethane. 106 The polyurethane increased stiffness of the graft and supported the in vitro 2D cell culture of HUVECs and normal hDFs (NHDFs) for 2 weeks.…”
Section: Two-dimensional Tissuementioning
confidence: 99%
“…[104][105][106] Wu et al circumvented the mechanical mismatch across the two species by covering the porcine aorta graft with electrospun polyurethane. 106 The polyurethane increased stiffness of the graft and supported the in vitro 2D cell culture of HUVECs and normal hDFs (NHDFs) for 2 weeks. 106 In a study by Negishi et al, sheets of porcine aorta were decellularized by using high hydrostatic pressure since traditional detergent-based methods of decellularization, including SDS and Triton X-100, did not work.…”
Section: Two-dimensional Tissuementioning
confidence: 99%
“…At present, large‐ and medium‐caliber blood vessels have been studied and matured, whereas small‐caliber blood vessels (diameter <6 mm) are prone to thrombosis during use. To solve the problem of embolisation of small blood vessels, much research effort has been devoted to the improvement of the preparation process and the selection of polymers [2, 4]. In this context, electrospinning technology has become a research hotspot for the development of biomaterials, since it can produce nano‐sized porous structures that can effectively simulate the composition and structure of the extracellular matrix.…”
Section: Introductionmentioning
confidence: 99%